Chapter 5 The Systems Approach to Innovation Management - Karlsson, Magnus (Routledge Companions in Business, Management and Accounting, 2019)
The environment in which a company or organization operates today can be characterized by accelerating change, the globalization of markets, the emergence of new technologies and competitors, new regulatory requirements and ever more demanding users and citizens. In this environment, the ability to innovate becomes a key success factor for most organizations. They seek to continuously create and realize value by introducing new or changed products, services, processes, models, methods, etc. The reasons for an organization to innovate are many and can include to increase revenues, growth and profitability, reduce costs and waste, increase the satisfaction of users, customers and citizens, motivate employees and attract partners, collaborators and funding, and so on. Engaging in innovation activities is thus a way for an organization to be future focused and effectively deliver on its overall objectives to secure prosperity and longer-term relevance and survival. The ability to innovate and to make it a core organizational capability is increasingly becoming the most important differentiator and dominant success factor of organizations. Failing to capture new opportunities and to respond to innovation challenges may consequently lead to stagnation, irrelevance and ultimately to the demise of the organization.